2018
DOI: 10.1155/2018/1785614
|View full text |Cite|
|
Sign up to set email alerts
|

Protective Effect of Ginkgo biloba and Magnetized Water on Nephropathy in Induced Type 2 Diabetes in Rat

Abstract: We aimed in our current study to explore the protective effect of Ginkgo biloba (GB) and magnetized water (MW) against nephrotoxicity associating induced type 2 diabetes mellitus in rat. Here, we induced diabetes by feeding our lab rats on a high fat-containing diet (4 weeks) and after that injecting them with streptozotocin (STZ). We randomly divided forty rats into four different groups: nontreated control (Ctrl), nontreated diabetic (Diabetic), Diabetic+GB (4-week treatment), and Diabetic+MW (4-week treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 54 publications
3
20
1
Order By: Relevance
“…Ginkgolides A, B and C. Decrease the level of ROS, the release of LDH, TNF-α, IL-1β and IL-6 and the expression of c-fos and c-jun mRNA; inhibits activation factor of platelets and of signaling pathway NIK/IKK α/IkB/NF-κB; increases cellular proliferation, activity of free radicals capture, activation of the p42/p44 (ERK) MAPK pathways, levels of mRNA and the protein from the HIF-1α. [38], the administration of EGB761 in mice with inducted DM2 resulted in the reduction of glycemia in a very significant way and reduced the levels of urea and creatinine in comparison to diabetic mice that were not treated. The work of Rhee et al [39] induced type 1 diabetes mellitus (DM1) and DM2 in mice and showed that the use of EGB761 reduced glycemia and levels of insulin.…”
Section: Compound Action Referencesmentioning
confidence: 89%
“…Ginkgolides A, B and C. Decrease the level of ROS, the release of LDH, TNF-α, IL-1β and IL-6 and the expression of c-fos and c-jun mRNA; inhibits activation factor of platelets and of signaling pathway NIK/IKK α/IkB/NF-κB; increases cellular proliferation, activity of free radicals capture, activation of the p42/p44 (ERK) MAPK pathways, levels of mRNA and the protein from the HIF-1α. [38], the administration of EGB761 in mice with inducted DM2 resulted in the reduction of glycemia in a very significant way and reduced the levels of urea and creatinine in comparison to diabetic mice that were not treated. The work of Rhee et al [39] induced type 1 diabetes mellitus (DM1) and DM2 in mice and showed that the use of EGB761 reduced glycemia and levels of insulin.…”
Section: Compound Action Referencesmentioning
confidence: 89%
“…Magnetic water has been shown to alter the pH of water to neutral or alkaline, which can mitigate the effects of oxidative stress. For example, Zayed et al (2018) found that providing MW to type 2 diabetic rats can reduce oxidative stress, hyperlipidemia, uremia, and renal dysfunction. In human, Weidman et al (2016) reported a relation between oxidative stress and blood viscosity.…”
Section: Resultsmentioning
confidence: 99%
“…In the biomedical field, provision of MW to rats for 30 days increased mineral density and mineral content of their bone compared to those of rats receiving non-magnetic water (Balieiro-Neto et al, 2017). In addition, providing MW to diabetic rats protected their kidneys from nephrotoxic damages as one of type 2 diabetes related complications (Zayed et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Previously, it was shown that EGb761 alleviated renal damage in a rat model of diabetic nephropathy [Zayed et al, 2018]. In this report, we investigated whether EGb761 exerted its protective effect on statin-induced myopathy via antagonizing the oxidative stress.…”
Section: Egb761 Reversed Sim-induced Changes In Gastrocnemius Muscle mentioning
confidence: 92%